BRANDING OF A SCIENTIFIC SOCIETY IN THE INTERNET SPACE (Journal of Information Technologies in Education (ITE), 2022)
The article raises a problem of image formation of a scientific society in the internet space. Activity of young scientists requires a regular promotion, and scientific work should be popularized among students, consequently the issue of brending a scientific society as a union, which functionates for the support of beginning researchers, creating conditions for their professional and personal realization and establishing partnerships with domestic and foreign organizations, has been highlighted. The goals and tools of branding as a modern marketing phenomenon are considered, in particular on the example of branding a higher education institution. It is proposed to apply the branding strategies of a higher education institution to a scientific society as a self-governing body, which includes students and young scientists of an educational institution. The role of the online-tools in the process of brend formation has been defined. The structure of the webpage of the Scientific society of the students, PhD-students, doctorants and young scientists of the Kherson State University in the official site of the educational institution has been characterized and the functions of the applied modules have been analyzed. Variants of partial elimination of the specified shortcomings, which simplify the moderation of the page, are given. The expediency of reorienting the functions of individual modules in order to rationally place content, establish relationships with other information resources, namely pages in social networks, and obtain additional analytical data that will have an impact on administering information resources for the selection and publication of content that best meets the requirements of users, and therefore corresponds to the interests of the target audience and contributes to increasing the coverage, is substantiated. The perspective of the research is the analysis of the Facebook page of the Scientific Society of students, PhD-students, doctorants and young scientists of the Kherson State University as a tool for presenting activities and interaction with the target audience in the Internet space.
Keywords: branding, webpage, higher education institution, young scientists, scientific society